Incidence of 'Precordial ST-Segment Depression' in Acute Inferior Myocardial Infarction (University Heart Journal, 2011)
Patients of acute inferior myocardial infarction, in addition to the ST segment elevation in inferior leads often have ST segment depression in the precordial leads. This study was performed to observe the incidence of these ‘reciprocal’ ST changes. One hundred consecutive acute inferior myocardial infarction patients were included in the study. They were further allocated to two electrocardiographic groups. Group 1 consisted of patients of acute inferior myocardial infarction with precordial ST segment depression & Group 2 consisted of patients of acute inferior myocardial infarction without precordial ST segment depression. Among the 100 consecutive patients, a large number of patients were included in group 1 (76%). Significant number of patients of group 1 belonged to the age group of above 60 years compared to group 2 (27.6% vs. 4.2%; p < .02). Conversely significantly higher number of younger patients ≤ 40 years belonged to group 2 (41.7% vs. 11.9%; p < .01). Mean ST segment elevation (mm) was also significantly higher in group 1 than group 2 (4.07 ± 1.93 vs. 2 ± 0.78; p